The Influence of Preceptorship Learning Method on Caring Behavior of Students at ICU Room - Sukartini, Tintin; Maulida, Enis Rezqi; Suarilah, Ira (International Journal of Psychosocial Rehabilitation, 2020)
Caring behavior is one of the benchmarks for the quality of nursing services. However, when providing nursing care, not all students can do it in the right way. The results of research conducted by using the Caring Behavior Inventory (CBI) in college students accounted for only 23% of subjects with good caring behaviors. While 54% was in the moderate category and 23% was in the less category. In this study, researchers used a pre- experimental group pre-posttest design. Caring behavior was the dependent variable and preceptorship learning was an independent variable. The total sample was 13 subjects conducted by nonprobability sampling. The data collection tool used is the Caring Behavior Inventory (CBI). Data were analyzed using a paired t-test with a significance level of 0.05. The results showed a significance value of 0.071. P value> 0.05 indicates that there is no influence of preceptorship learning on the caring behavior of a student in the ICU. This indicates the need for further research on preceptorship learning programs and their influence on the caring behavior of nursing students.